All‐trans retinoic acid upregulates the expression of ciliary neurotrophic factor in retinal pigment epithelial cells. (June 2017) - Zhou, Wen‐Di; Wang, Lu‐Lu; Zhou, Lan‐Bo; Bin, Wei; Bao, Tian‐Ping; Zhang, Yi; Shu, Jin; Yang, Wei‐Xia; Hui, Liang‐Liang; Jin, Rui; Zhuang, Li‐Li; Zhou, Guo‐Ping
Abstract : Retinopathy of prematurity, a leading cause of visual impairment in low birth‐weight infants, remains a crucial therapeutic challenge. Ciliary neurotrophic factor (CNTF) is a promyelinating trophic factor that promotes rod and cone photoreceptor survival and cone outer segment regeneration in the degenerating retina. Ciliary neurotrophic factor expression is regulated by many factors such as all‐trans retinoic acid (ATRA). In this study, we found that ATRA increased CNTF expression in mouse retinal pigment epithelial (RPE) cells in a dose‐ and time‐dependent manner, and PKA signaling pathway is necessary for ATRA‐induced CNTF upregulation. Furthermore, we showed that ATRA promoted CNTF expression through CREB binding to its promoter region. In addition, CNTF levels were decreased in serum of retinopathy of prematurity children and in retinal tissue of oxygen‐induced retinopathy mice. In mouse RPE cells cultured with high oxygen, CNTF expression and secretion were decreased, but could be recovered after treatment with ATRA. In conclusion, our data suggest that ATRA administration upregulates CNTF expression in RPE cells.